DAMPAK WACANA KENAIKAN PPN 12% BAGI PELAKU UMKM DI SURABAYA - Kisdayanti, Lelli; Farida, Nur (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The planned increase in the Value Added Tax (VAT) rate from 11% to 12%, scheduled to take effect in January 2025, could have significant impacts on Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in Surabaya. This study aims to analyze the effects of the VAT increase on production costs, consumer purchasing power, and the responses taken by MSME owners in facing this policy change. The research employs a qualitative approach with a case study design, where data is collected through in-depth interviews and surveys with MSME owners from various sectors. The findings suggest that the VAT increase is likely to raise operational costs and product prices, which could reduce consumer demand. However, some MSME owners have responded by adopting strategies such as increasing efficiency, innovating products, and adjusting prices to maintain competitiveness. The government is also expected to provide support through policies like subsidies or tax incentives to help MSMEs survive and thrive amid these challenges